D- and z-values of Escherichia coli O157 H7, Salmonella enterica, and Listeria monocytogenes in heated orange juice - Pagal, Gladess A.; Gabriel, Alonzo A. (2020)
This study was conducted to determine the decimal reduction times (D) and the thermal resistance parameter (z) values of relevant foodborne pathogens linked with fruit juice consumption ?namely Escherichia coli O157:H7, Salmonella enterica, and Listeria monocytogenes. Cocktails of different strains of the same bacterial species were prepared and thereafter subjected to thermal inactivation studies at 50, 53, 55, 57, and 60 °C heating temperatures in orange juice. Survivor populations were determined by surface-plating onto a non-selective medium, after which the inactivation behavior and kinetic parameters were determined. Results showed that for all tested organisms, the D-values significantly (P < 0.05) decreased with increasing heating temperature. In all heating temperatures, E. coli O157:H7 exhibited the significantly greatest heat resistance, with D-values ranging from 324.60 s to 95.12 s. At 50 °C, L. monocytogenes (D-values 152.32 s to 11.84 s) was significantly more resistant than S. enterica (D-values 106.55 s to 19.29 s). At higher heating temperatures, the D-values of S. enterica and L. monocytogenes were not significantly different (P > 0.05). The calculated z-values significantly varied across the test organisms, which ranged from 9.40 °C (L. monocytogenes) to 18.78 °C (E. coli O157:H7). These results may be used in the establishment of new, and validation of existing, thermal process schedules to ensure safety against the test pathogens. (Author's abstract)
Includes bibliographical references (pages 267-268)
Keywords: D-value.; Orange juice; Pathogens; Thermal inactivation; Thermal processing; Z-value.